Infringement of intellectual property rights over the Internet and private international law - Yang, Fanshu (2010)
With the advent of the Internet, some new problems in the field of intellectual property law have appeared. The infringement of intellectual property rights (IP infringement) over the Internet is one of them. The purpose of my study is to try to find the solution to the problem of IP infringement over the Internet in the field of private international law, focusing on jurisdiction rules. First of all, in Chapter 2, I examine infringements of trademark, copyright and patent over the Internet respectively. After having examined the current situation of Internet IP infringement, I discuss the solutions that technology development and substantive law provide in Chapter 3. But neither of them can solve it. As such infringement often has connections with many countries, the court has to first consider jurisdictional problems. In Chapter 4, we have a general view about how jurisdictional problems have arisen in Internet IP infringement. From Chapter 5, we go into the details of how private international law can solve the problem of Internet IP infringement. In Chapter 5, we consider how the Brussels regime deals with this problem. We will examine how Article 22(4), Article 2, Article 5(3) and Article 6(1) of the Brussels I Regulation can be applied to Internet IP infringement. Where the defendant to an Internet IP infringement is not domiciled within a Member State, the English rules will apply. In Chapter 6, we examine how the English rules deal with such infringement. We will focus on how para.3.1 of Practice Direction 6 B applies in Internet IP infringement. After considering the existing jurisdiction rules, we have seen many difficulties in applying them to IP infringement over the Internet. Thus, the reform is needed. Several reform options will be examined in Chapter 7, and we will choose the best one.